National quality campaigns: who benefits?. Issue 4 (9th June 2010) - Hansen, Luke O; Herrin, Jeph; Nembhard, Ingrid M; Busch, Susan; Yuan, Christina T; Krumholz, Harlan M; Bradley, Elizabeth H
Abstract : Background: The use of national quality campaigns to foster evidence-based hospital practices is increasing. Because campaigns typically do not limit access to their resources, they may influence non-enrolled hospitals as well. Objective: To examine the relative impact of a national campaign, the Door-to-Balloon (D2B) Alliance, on enrolled and non-enrolled hospitals. Methods: In this prospective cohort study, we compared the use of D2B Alliance resources (eg, webinars, online community, mentor network), changes in the use of strategies recommended by the D2B Alliance, and perceived impact of the D2B Alliance between hospitals that enrolled in the D2B Alliance (n=264) and hospitals that declined enrolment (n=101). Results: More than half (53.2%) of non-enrolled hospitals reported using at least some of the resources made available by the D2B Alliance to improve door-to-balloon times. This compared with 83.5% of enrolled hospitals reporting that they used D2B Alliance resources (p<0.01). Both enrolled and non-enrolled hospitals significantly increased their use of recommended hospital strategies between 2005 and 2008, although the use of strategies remained incomplete (35.5–91.5% use). There was no significant difference between the use of these strategies between enrolled and non-enrolled hospitals at follow-up (p≥0.51), adjusted for baseline use. About half of all hospitals reported that door-to-balloon times would have been worse at their hospital without the existence of the D2B Alliance. Conclusions: This research suggests that national quality campaigns with open access to campaign resources may have substantial spillover effects on non-enrolled hospitals.